Sino-LAC ties: Trade relationships and asymmetric dependency - Devadason, E.S.; Chandran, V.G.R.; Mubarik, S. (2015)

(untitled)
Previous studies have emphasized the asymmetry in the Sino-LAC partnership, solely based on their trade exchanges. This paper extends the boundaries of understanding structural asymmetries in the Sino-LAC trade, by considering unequal opportunities in this partnership. The latter is accounted for by deriving two-way export potentials from the Sino-LAC partnership. The analysis is pitched within China's multiple trade interactions with global partners, to reflect a broader internationalized concept of potential in terms of exports. On average, the gravity of LAC's trade promise with China appears to lie in continuing to grow the level of exports in agriculture. Incontrast, the model finds China to be exporting at predicted levels to LAC, and over-exporting in manufactures. These results lend support to the recent observation that China-LAC trade may have hit a plateau. The aggregate results, further, obscure opportunities for exports of manufactures from countries such as Argentina and Mexico to China (albeit marginal). Therefore, the export potentials observed for LAC to China, instead of China to LAC, not only imply untapped possibilities for the former relative to the latter connection, but also indicate their disparate opportunities for further integration; it is therefore misleading to draw inferences of asymmetry solely based on stylistic trends of exchanges, largely explained by the magnitude, concentration and structure of exports.